Evaluation of Functional Outcome Following Hybrid External Fixation in The Management of Schatzkers Type V and VI Tibial Plateau Fractures - A Prospective Study of 30 Patients - Subash, Y (Malays Orthop J, 2021)
INTRODUCTION: Fractures of the proximal tibia are high velocity injuries often associated with soft tissue compromise especially in the type V and VI fracture patterns. Dual plating is the preferred treatment option for these injuries but not in a setting where there is extensive soft tissue injury, as this can lead to problems with wound healing. The aim of this study was to evaluate the functional outcome following hybrid external fixation in the management of Schatzkers type V and VI fractures. MATERIALS AND METHODS: A total of 30 patients with type V and VI proximal tibial fractures who presented between January 2012 to January 2015 were managed with hybrid external fixation and were followed-up for a period of 3 years. RESULTS: The mean age of the patients was 42.26 years with the left knee being more commonly affected. Schatzkers type V was the more common fracture type seen. The mean time to union was 12.06 weeks and the average range of motion achieved was 0 to 100°. The mean Rasmussens functional score was 25.4 at last follow-up and we had excellent results in 5 patients and good results in 22 patients. CONCLUSION: Through this study, we conclude that the hybrid external fixation is an excellent option in the type V and VI fractures with extensive soft tissue compromise. It is easy to apply, facilitates early mobilisation of the joint and gives good functional results.